Research recast(ed): S4E4 - Is it a ghost or is it your mind? - Leschyshyn, Brooklyn; Smadis, Natalie; Schmaltz, Rodney (My University, 2024)
On today’s episode we are joined by Dr. Rodney Schmaltz as he explores scientific skepticism. We talk about how he guides students in creating protocols for the $500,000 Paranormal Challenge, testing claims like telekinesis and psychic abilities. Dr. Schmaltz highlights the difference between skepticism and cynicism, examines the role of expectation in paranormal experiences, and discusses infrasound's impact on hauntings.
Keywords: scientific skepticism; paranormal; expectation; infrasound